2015
DOI: 10.1371/journal.pone.0130371
|View full text |Cite
|
Sign up to set email alerts
|

Genome Regions Associated with Functional Performance of Soybean Stem Fibers in Polypropylene Thermoplastic Composites

Abstract: Plant fibers can be used to produce composite materials for automobile parts, thus reducing plastic used in their manufacture, overall vehicle weight and fuel consumption when they replace mineral fillers and glass fibers. Soybean stem residues are, potentially, significant sources of inexpensive, renewable and biodegradable natural fibers, but are not curretly used for biocomposite production due to the functional properties of their fibers in composites being unknown. The current study was initiated to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Studies applying SbS (soybean straw) residues in the production of composites have been developed (REINPRECHT et al, 2015;SITZ;BAJWA, 2015;SHAO;JIANG, 2016;MARTELLI-TOSI et al, 2017) and showed positive results in comparison to traditional materials (e.g. timber, plywood and fiberboards), although these composites are classified as non-structural according to EN 300 standard (EUROPEAN…, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Studies applying SbS (soybean straw) residues in the production of composites have been developed (REINPRECHT et al, 2015;SITZ;BAJWA, 2015;SHAO;JIANG, 2016;MARTELLI-TOSI et al, 2017) and showed positive results in comparison to traditional materials (e.g. timber, plywood and fiberboards), although these composites are classified as non-structural according to EN 300 standard (EUROPEAN…, 2006).…”
Section: Introductionmentioning
confidence: 99%